Expression, purification and structural analysis of functional GABA transporter 1 using the baculovirus expression system - Hu, Jing; Weise, Chris; Böttcher, Christoph; Fan, Hua; Yin, Jian (Beilstein Journal of Organic Chemistry, 2017)
The γ-aminobutyric acid (GABA) transporter 1 (GAT1) belongs to a family of Na+ and Cl−-coupled transport proteins and possesses 12 putative transmembrane domains. To perform structural analyses of the GAT1 protein, the GAT1/green fluorescent protein (GFP) fusion protein was functionally expressed in insect Sf9 cells by the BAC-TO-BAC® baculovirus expression system. A two-step procedure to purify the GAT1/GFP fusion protein from insect Sf9 cells has been established and involves immunoaffinity chromatography using self-prepared anti-GFP antibodies and size-exclusion fast protein liquid chromatography (SE-FPLC). A yield of 200–300 μg of the GAT1/GFP protein could be purified from 400–600 mL of infected Sf9 cells. The purified protein was analyzed by transmission electron microscopy (TEM), which revealed that the GAT1/GFP fusion protein was isolated in its monomeric form.
Keywords: baculovirus expression system; chromatography; γ-aminobutyric acid (GABA); GABA transporter 1 (GAT1)